PERBANDINGAN EFEKTIVITAS TERAPI AKUPRESUR TITIK KOMBINASI LR3 DAN DU20 DENGAN TITIK TUNGGAL LR3 TERHADAP NYERI DISMENORE PADA REMAJA PUTRI MAN 2 PEKANBARU - Indah Afriani; Oswati Hasanah; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
In fact, many teenagers experience menstrual problems, including menstrual pain or dysmenorrhea. Dysmenorrhea can be treated with pharmacological and non-pharmacological therapies, one of them is acupressure. Acupressure  is a traditional treatment by pressing certain points on the skin surface using fingers or a blunt object.The purpose of this study was to compare the effectiveness of the combination point acupressure therapy LR3 and DU20 with single point LR3 on dysmenorrhea pain in adolescent girls at MAN 2 Pekanbaru. This research is an experimental study, with a population of 354 students and a sample of 70 students who have dysmenorrhea. The analytical technique used to see the comparison is by using the independent sample T test. Based on the results of the independent sample T test, sig = 0.889> 0.05, it can be concluded that there is no difference in the effectiveness of the combination point acupressure therapy LR3 and DU20 with a single point LR3 on dysmenorrhea pain in adolescent girls at MAN 2 Pekanbaru. This condition could be caused by the difference in the intervention of the two therapies is not too significant.Keywords: Combination Point Acupressure, Single Point Acupressure, Dysmenorrhea